Uncovering new frontiers: A scientometrics investigation of synergies between the helix model and open innovation theories - Haziman, Zakaria; Fernando, Yudi; Diyana, Kamarudin; Yuserrie, Zainuddin (Emerald Publishing, 2025)
Purpose This paper aims to investigate the helix model theory and open innovation theory, which are vital in the field of innovation and technology management. The objective is to establish a connection between these theories in the literature by using bibliographic coupling and co-occurrence analysis. This analysis aims to anticipate industrial trends and assess how they align with the sustainable development goals.